Akutni koronarni sindrom (STEMI, NSTEMI i nestabilna angina pektoris) i faktori rizika, sličnosti i razlike - Mihajlović, Dalibor; Maksimović, Žana M.; Dojčinović, Boris; Banjac, Nada (Scripta Medica, 2020)
Introduction: Acute coronary syndrome (ACS) is one of the most common and most dramatic manifestations of ischaemic heart disease and distinguishing of ACS from non-cardiac chest pain represents a diagnostic challenge. Objective: Determine the frequency of ACS types: NSTEMI, STEMI and unstable angina pectoris (UAP) and examine the frequency and significance of risk factors and cardiospecific enzymes in patients with ACS.Methods: The analysis included patients who were referred from the prehospital level of the Banja Luka Primary Healthcare Centre (Emergency Department and Family Medicine Department) and treated under the ACS diagnosis in the coronary unit of the Cardiovascular Diseases Clinic of the Banja Luka University Clinical Centre of the Republic of Srpska (UCCRS) in the first 6 months of 2011. The study included patients older than 18, with recorded information on their gender, age, smoking status, hypertension, diabetes, obesity and family burden. Values of cholesterol, triglycerides, serum potassium, creatine kinase (CK), CK-MB, cardiac troponin T (cTnT) were measured.Results: The total of 192 patients were referred under the referral diagnosis of ACS and treated in the coronary unit of the CVD Clinic of the Banja Luka UCCRS. At the same time, ACS was confirmed in 178 cases. STEMI was confirmed in 86 patients (48.31 %), NSTEMI in 55 (30.90 %) and UAP in 37 (20.79 %). ACS was statistically significantly more common in men (112 men and 66 women), in particular younger men (average age for men was 62.7 and 69.2 for men and women, respectively) (U = 2.472 · 103 , p < 0.001). Among the risk factors, it was found that smoking was more often associated with STEMI (p = 0.014) and hypertension with UAP (p = 0.041). Among all parameters, all three examined cardiac biomarkers showed statistical significance (p < 0.001), namely: values at STEMI > NSTEMI > UAP.Conclusion: Half of patients with ACS did not have STEMI (which is presumably easy to diagnose). Third of patients with ACS reported atypical symptoms, which further complicates the early recognition of MI without ST elevation. Precaution is needed in women and in elderly. Determination of cTnT should be available in every examination room.
Keywords: Akutni koronarni sindrom; NSTEMI; Faktori rizika; CK-MB; cTnT